Two novel variations in LRP2 cause Donnai-Barrow syndrome in a Chinese family with severe early-onset high myopia - Yuan, Shiqin; Huang, Xiaoyu; Zhang, Shuang; Yang, Shangying; Rui, Xue; Qi, Xiaolong; Wang, Xuhui; Zheng, Yali; Rong, Weining; Sheng, Xunlun (Frontiers in Genetics, 2023)
Donnai-Barrow syndrome (DBS) is a rare autosomal recessive disorder caused by mutation in the low density lipoprotein receptor-related protein 2 gene (LRP2). Defects in this protein may lead to clinical multiple organ malformations by affecting the development of organs such as the nervous system, eyes, ears, and kidneys. Although some variations on LRP2 have been found to be associated with DBS, early diagnosis and prevention of patients with atypical DBS remains a challenge for many physicians because of their clinical heterogeneity. The objective of this study is to explore the association between the clinical presentation and the genotype of a DBS patient who was initially diagnosed with early-onset high myopia (eoHM) from a healthy Chinese family. To this end, we tested the patient of this family via whole exome sequencing and further verified the results among other family members by Sanger sequencing. Comprehensive ophthalmic tests as well as other systemic examinations were also performed on participants with various genotypes. Genetic assessment revealed that two novel variations in LRP2, a de novo missense variation (c.9032G>A; p.Arg3011Lys) and a novel splicing variation (c.2909-2A>T) inherited from the father, were both carried by the proband in this family, and they are strongly associated with the typical clinical features of DBS patients. Therefore, in this paper we are the first to report two novel compound heterozygous variations in LPR2 causing DBS. Our study extends the genotypic spectrums for LPR2-DBS and better assists physicians in predicting, diagnosing, and conducting gene therapy for DBS.